Scintillation Effect on Satellite Communications within Standard Atmosphere - Ali Hussein, Mohammed (Anbar Journal of Engineering Sciences, 2009)
In satellite communications with frequencies above 10GHz the major problems in radio-wave propagation is signal level attenuation caused by tropospheric scintillation, together with signal level attenuation by rain. There are several methods to measure the magnitude of scintillation. The equations of most of these methods do not include meteorological element. In meantime we can not measure the magnitude of scintillation with elevation angle 5¢ھ-10¢ھ. A prediction method is suggested to measure tropospheric scintillation on earth-space path. It would apply this method to standard atmosphere and we studied the effect of meteorological conditions, frequency, antenna diameter and elevation angle on the magnitude of scintillation.